Knowledge of nursing professionals about palliative care (Research, Society and Development, 2021)
The aim of this study was to assess the knowledge of the nursing staff about palliative care (PC) in Basic Health and Family Strategy Units  and hospital inpatient units. This is a cross-sectional study, developed in the inpatient units of a public hospital and two Basic Health Family Strategy Units, in a country town of São Paulo. Twelve nurses and five nursing assistants/technicians from Basic Health Family Strategy Units and ten nurses and 43 hospital assistants/technicians participated in the study, totaling 70 professionals who had worked in the units for 12 months or more. Data were collected through two questionnaires, one with sociodemographic data and the other with 30 statements about PC, data that were analyzed in a descriptive and inferential way. It was found that 76.66% of the professionals got the questions of general knowledge about PC. Only 18.75% of the nursing assistants/technicians and 36.36% of the nurses agreed on the definition of dysthanasia and orthothanasia, 70.83% of the assistants/technicians and 54.55% of the nurses. There is a statistical trend between the number of correct answers with the time of  experience and those who took a specific PC course. It was concluded that basic aspects of palliative care should be part of in-service education; It is important for professionals to understand that the care plan should not shorten life, but offer quality of life to patients until the last moment of their life. It is believed that this study can contribute to a reflection on teaching-learning and professional training.